2022
DOI: 10.2460/javma.21.06.0320
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in a veterinary outpatient community medicine setting has a good outcome for dogs with pyometra

Abstract: OBJECTIVE To compare the outcome of canine pyometra surgeries performed at referral hospitals with those performed at community clinics (outpatient settings), and to evaluate factors that impact outcome. ANIMALS 133 client-owned dogs with pyometra treated with ovariohysterectomy (OHE) at 2 community clinics or 2 referral hospitals between July 1, 2017, and June 30, 2019. PROCEDURES A retrospective electronic medical record search was used to identify eligible cases. Data about patient demographics and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Previous research has demonstrated no difference in mortality or long-term outcome between patients treated in an outpatient clinic as compared to an inpatient clinic, indicating that some additional treatments may be unnecessary for patient survival and long-term return to function. [11][12][13][14][15] Of those pyometra cases declined treatment at a HQHVSNC or PP, poor prognosis was a common reason for euthanasia. While the surveys used for the current study and other research indicate a high survival rate for patients that undergo surgical treatment for pyometra, [11][12][13][14][15]18,19 animals euthanized before surgery may not be included in these statistics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated no difference in mortality or long-term outcome between patients treated in an outpatient clinic as compared to an inpatient clinic, indicating that some additional treatments may be unnecessary for patient survival and long-term return to function. [11][12][13][14][15] Of those pyometra cases declined treatment at a HQHVSNC or PP, poor prognosis was a common reason for euthanasia. While the surveys used for the current study and other research indicate a high survival rate for patients that undergo surgical treatment for pyometra, [11][12][13][14][15]18,19 animals euthanized before surgery may not be included in these statistics.…”
Section: Discussionmentioning
confidence: 99%
“…18 Two settings for pyometra treatment are highquality, high-volume spay-neuter clinics (HQHVSNCs) and private practices (PPs). 12,18,19 High-quality, highvolume spay-neuter clinics specialize in efficient, cost-effective sterilization surgeries, including ovariohysterectomies, 12,19,21 whereas PPs offer a wider array of care options for both sick and well pets. 18 This manuscript compares results from 2 previously published surveys aimed at determining how pyometra is treated in HQHVSNCs 19 and PPs.…”
mentioning
confidence: 99%
“…For the type of treatment used, it was observed that in all cases the ovariohysterectomy technique was recommended. This fact may be related to the number of patients in severe condition and the lack of interest in maintaining reproductive activity, moreover, this surgical technique is considered the treatment of choice for cases of pyometra (Fieni et al, 2014;McCobb et al,…”
Section: Discussionmentioning
confidence: 99%
“…Both sets of authors also found that for canine pyometra cases, a surgical delay was not necessarily associated with a change in patient outcome. 2,4 The ability to delay canine pyometra surgery without compromising patient care is advantageous as clinics manage increasingly busy days. Pailler et al 3,4 also define prognostic markers for feline and canine pyometra cases that are associated with longer hospitalization times, thereby improving the ability to identify cases that need extended care.…”
Section: Small Animalsmentioning
confidence: 99%